MIGRASI BERULANG TENAGA KERJA MIGRAN INTERNASIONAL: KASUS PEKERJA MIGRAN ASAL DESA SUKOREJO WETAN, KABUPATEN TULUNGAGUNG - Mita Noveria (Jurnal Kependudukan Indonesia, 2017)
Working overseas is an attempt to earn higher income and to accumulate financial capitals to run small enterprise in migrants’ place of origins. In fact, many Indonesia returned migrants decided to re-migrate, either to previous countries or to new destination countries. This paper aims to assess factors that cause remigration of the returned labor migrants. This study used quantitative and qualitative data, based on research in one of major international labor migrants sending village in Indonesia, namely Sukorejo Wetan in Tulungagung District. Quantitative data was collected through survey on selected households, while qualitative data was gathered by in-depth interview, focus group discussion (FGD), and observation. The analysis shows four dominant factors that caused returned migrants to re-migrate, namely: (1) the remittances only sufficed consumption needs; (2) the returned migrants faced difficulties in adapting to labor force conditions at place of origins (i.e., job scarceness and low wage); (3) limited ability in entrepreneurship; and (4) availability of social network that facilitates remigration.